Clinical outcomes in acute pancreatitis with relative bradycardia at fever onset. Issue 46 (19th November 2021) - Okamoto, Takeshi; Arashiyama, Makoto; Nakamura, Kenji; Tsugitomi, Ryosuke; Fukuda, Katsuyuki
Abstract : Abstract: While some acute pancreatitis (AP) patents with fever do not exhibit a corresponding increase in heart rate, the clinical significance of this phenomenon has not been studied. We investigated the clinical relevance of relative bradycardia (RB) in febrile AP. A retrospective electronic chart review was conducted on consecutive patients admitted for AP at a tertiary referral center in Japan from January 1, 2010, to May 31, 2018. Presence of RB was determined at the first instance of fever, based on formulas used in previous studies. Fever at or during admission was observed in 115 patients, of which 33% had RB. Fever was observed at presentation in 48% and within 48 hours in 94% of cases. Etiologies were alcoholic in 48% and gallstones in 17% of cases. RB patients were older (median age: 62 vs 51 years, P  = .028) but had shorter median postfever lengths of stay (8 vs 12 days, P  = .003), lower median Ranson scores (1 vs 2, P  < .001), and were less likely to develop delirium (11% vs 38%, P  = .002). Nineteen of 21 severe AP cases based on the Ranson score were nonbradycardia ( P  = .011). RB was also associated with lower white blood cell count, C-reactive protein, and lactate levels. On computed tomography, necrosis ( P  = .028) and moderate or severe pancreatitis ( P  = .041) were less frequently observed in patients with RB. There was a significant inverse correlation between RB and the Ranson score (−.305, P  = .001). While RB was an independent predictors of postfever length of stay (LOS) in multiple regression analysis when the Ranson score was excluded ( P  = .010), it ceased to be significant when the Ranson score was included ( P  = .141). AP patients with RB at fever onset had milder disease and shorter LOS compared to those with higher heart rates at fever onset. RB may be useful as a simple, early predictor of shorter LOS before the Ranson score can be calculated.